From aid to development : the global fight against poverty - Keeley, Brian (OECD Publishing ParisFR, 2012)
Looks at the way development and aid have evolved, how the development landscape is changing, and how a new era of development partnerships can be built on the new commitments established at the Busan High-Level Forum in December 2011, and the new OECD Development Strategy.